PERANCANGAN BUKU ANEKA RESEP JAJANAN PASAR TRADISIONAL DI KOTA PADANG - CHENTI KOFI NOVELA, Dr. Budiwirman, M.Pd, Yofita Sandra, S.Pd., M.Pd (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Tradisional snacks in one component in everyday in life. Not only bacause of tradisional snackstaste good or unique color and appearance, but also because the tradisional snacks are valuable ancestral cultural heritage deriveed from earlier ancestors. But today’s current society has lost of modern snacks modern, then ignored tradisional snacks.The design of this book aims to remind the public to the importance of the existing tradisional hawker markets, necessitating, a variety of recipe books snacks that can assist in making tradisional snacks of processed foods, so the quality is safe and secure.Based on the results of various design book of tradisional recipes snacks can be a concern for people, especially those who have forgotten the kinds of snacks, so that with the book design of various recipes of tradisional snacks can make the community will get to know more of the snacks about their own tradisional snacks.Keyword: Design, Various Recipe Books Snacks, Padang City